Perlindungan Konsumen Terhadap Praktik Etika Bisnis Pinjaman Online Berupa Suku Bunga yang Besar - Zahra, Maulida; Amalliah, Putri Rizki; Maida, Shelomita Alywen; Widyaswara, Tsuraya (Peneliti.net, 2024)
The development of technology has had an impact on the social economic sector, especially through the growth of fintech companies that provide online lending services. This development has made it easier for individuals to obtain funds quickly to meet their living needs. This research aims to analyze the impact of high-interest online loans on consumers, and identify any business ethics violations committed by illegal fintech companies in Indonesia. The research method used is qualitative. The technique of collecting data uses literature study techniques. All the collected data is then analyzed descriptively. The research conclude that although there are regulations governing online loan services in Indonesia, including the maximum interest rate set by the Indonesian Fintech Lending Association (AFPI) for online loans registered with the Financial Services Authority (OJK), there are still many illegal online loan providers that pose risks to consumers with high interest rates.